The personal and contextual factors that affect customer experience during rail service failures and the implications for service design. (July 2020) - Ross, Tracy; May, Andrew; Cockbill, Stuart A.
Abstract: This paper: identifies personal and contextual factors that influence customer experience when service failures occur in rail transport; what is being conveyed through that factor (e.g. older age being used to convey vulnerability); and the implications for future service design. The results are from a thematic analysis of free-text rail passenger complaints (n = 516) reporting service failures that impacted on customer experience. The study differs from existing research on the pertinent personal and contextual factors for public transport service provision in that it: focuses on the passenger experience resulting from specific incidents (rather than evaluative, overall assessments of satisfaction), generates the factors inductively from the data (rather than a-priori) and uses detailed qualitative cases (rather than quantitative survey data). The findings (1) identify some similar factors to those used in previous research and uncover some new factors for both person and context, (2) provide an understanding of what they mean in terms of the passenger experience and (3) indicate how the factors might need to be measured if they are to be used by the rail industry. The paper concludes by using the outcome of an industry-based validation exercise to describe how the findings could be used in future rail services, namely: predicting where the customer experience is going to be sub-optimal, prioritising responses to particular circumstances, and designing services to better meet customer's needs. This exploratory research is timely, given the need for a more passenger-centric approach to service design and future developments such as smart-ticketing, which could potentially enable greater understanding of who is using the rail network and for what journeys. Highlights: Content analysis of relevant personal and contextual factors in 516 rail complaints. Focused on the factors that have an influence on passenger experience. A bottom-up, qualitative, data driven methodology led to rich data. Uncovered new factors that can complement existing market segmentation research. Identified how future rail services could use the personal and contextual factors.